Structural insight into the self-activation and G-protein coupling of P2Y2 receptor - Baoliang Lan; Shuhao Zhang; Kai Chen; Shengjie Dai; Jiaqi Fei; Kaixuan Gao; Xiaoou Sun; Bin Lin; Xiangyu Liu (Cell Discovery)
Abstract Purinergic P2Y2 receptor (P2Y2R) represents a typically extracellular ATP and UTP sensor for mediating purinergic signaling. Despite its importance as a pharmacological target, the molecular mechanisms underlying ligand recognition and G-protein coupling have remained elusive due to lack of structural information. In this study, we determined the cryo-electron microscopy (cryo-EM) structures of the apo P2Y2R in complex with Gq, ATP-bound P2Y2R in complex with Gq or Go, and UTP-bound P2Y4R in complex with Gq. These structures reveal the similarities and distinctions of ligand recognition within the P2Y receptor family. Furthermore, a comprehensive analysis of G-protein coupling reveals that P2Y2R exhibits promiscuity in coupling with both Gq and Go proteins. Combining molecular dynamics simulations and signaling assays, we elucidate the molecular mechanisms by which P2Y2R differentiates pathway-specific Gq or Go coupling through distinct structural components on the intracellular side. Strikingly, we identify a helix-like segment within the N-terminus that occupies the orthosteric ligand-binding pocket of P2Y2R, accounting for its self-activation. Taken together, these findings provide a molecular framework for understanding the activation mechanism of P2Y2R, encompassing ligand recognition, G-protein coupling, and a novel N-terminus-mediated self-activation mechanism.